PERBEDAAN PENGETAHUAN IBU RUMAH TANGGA SEBELUM DAN SESUDAH DIBERI SOSIALISASI PENCEGAHAN HIV/AIDS DI DESA SOKARAJA KULON KECAMATAN SOKARAJA KABUPATEN BANYUMAS - Muflihah, Ima Syamrotul; Lestari, Endang; Margiana, Wulan; Atmarina, Diah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
ABSTRACT: DIFFERENCES IN KNOWLEDGE HOUSEWIFE BEFORE AND AFTER GIVEN THE SOCIALIZATION ON THE PREVENTION OF HIV/AIDS IN THE VILLAGE SOKARAJA KULON REGENCY SOKARAJA DISTRICT BANYUMAS. HIV/AIDS can be at risk in all populations both in men and women, which one of the population at risk is a housewife. The housewives are largely infected by their husbands who have sex carelessly. There are 53.1% of men are considered to have a tendency of cheating. This means that women who do not know anything can be affected by HIV/AIDS as a result of the husband's deviant sexual behavior. This proves the weak position  of  wife’s  (female)  knowledge.  One  of  the efforts  to  suppress  the  spread  of HIV/AIDS in the housewife can be increased the comprehension and awareness of the dangers of HIV/AIDS in the family which being delivered through socialization about HIV/AIDS prevention by KPA of Banyumas for the housewives, so that they can conduct the prevention efforts of HIV/AIDS transmission. This study aimed to analyze the difference in housewife’s knowledge between before and after given socialization about HIV/AIDS prevention at Sokaraja Village Sokaraja Sub-district Banyumas Regency. This was a preexperimental study. This study used one group pretest-posttest design with intervention of the socialization about HIV/AIDS preventions. The population in this study  was  all  the  housewives  at  Sokaraja  Village  Sokaraja  Sub-district  Banyumas Regency as many as 892 women. The samples in this study were 27 respondents that sampel by using purposive sampling technique. The data instrument used questionnaires. And the data were analyzed by using the marginal homogeneity test. The results of this study  indicate  that  before  given  socialization  the  housewife  have  knowledge  in  the category of low, medium, and high as many as 16 respondents (69.3%), 9 respondents (33.3%) and 2 respondents (7.4%), respectively. And after given socialization, the housewife have knowledge in the category of low, medium, and high as many as 4 respondents (25.9%), 9 respondents (33.3%) and 11 respondents (40.7%), respectively. There is a difference in the housewife’s knowledge between before and after given socialization about HIV/AIDS prevention with p value of 0.000 <α (0.05).  Keywords: Knowledge, HIV/AIDS